Variation and stability of rhizosphere bacterial communities of Cucumis crops in association with root-knot nematodes infestation - Song, Liqun; Ping, Xingxing; Mao, Zhenchuan; Zhao, Jianlong; Yang, Yuhong; Li, Yan; Xie, Bingyan; Ling, Jian (Frontiers in Plant Science, 2023)
Root-knot nematodes (RKN) disease is a devastating disease in Cucumis crops production. Existing studies have shown that resistant and susceptible crops are enriched with different rhizosphere microorganisms, and microorganisms enriched in resistant crops can antagonize pathogenic bacteria. However, the characteristics of rhizosphere microbial communities of Cucumis crops after RKN infestation remain largely unknown. In this study, we compared the changes in rhizosphere bacterial communities between highly RKN-resistant Cucumis metuliferus (cm3) and highly RKN-susceptible Cucumis sativus (cuc) after RKN infection through a pot experiment. The results showed that the strongest response of rhizosphere bacterial communities of Cucumis crops to RKN infestation occurred during early growth, as evidenced by changes in species diversity and community composition. However, the more stable structure of the rhizosphere bacterial community in cm3 was reflected in less changes in species diversity and community composition after RKN infestation, forming a more complex and positively co-occurrence network than cuc. Moreover, we observed that both cm3 and cuc recruited bacteria after RKN infestation, but the bacteria enriched in cm3 were more abundant including beneficial bacteria Acidobacteria, Nocardioidaceae and Sphingomonadales. In addition, the cuc was enriched with beneficial bacteria Actinobacteria, Bacilli and Cyanobacteria. We also found that more antagonistic bacteria than cuc were screened in cm3 after RKN infestation and most of them were Pseudomonas (Proteobacteria, Pseudomonadaceae), and Proteobacteria were also enriched in cm3 after RKN infestation. We hypothesized that the cooperation between Pseudomonas and the beneficial bacteria in cm3 could inhibit the infestation of RKN. Thus, our results provide valuable insights into the role of rhizosphere bacterial communities on RKN diseases of Cucumis crops, and further studies are needed to clarify the bacterial communities that suppress RKN in Cucumis crops rhizosphere.